ФРАЗЕОЛОГИЗМЛЕР ҚУРАМЫНДА «АҚ» ҲӘМ «ҚАРА» РЕҢ СЕМАНТИКАСЫНЫҢ ҚОЛЛАНЫЛЫЎЫ - Алламбергенова, Г. (FAN va JAMIYAT, 2020)
The article studies phraseological units that express the appearance and color. In fact, in linguistics, colors make up a lexical group of words. It is known various idioms, proverbs and sayings associated with colors are used in the language. The colors as a part of phraseological units can be studied separately according to their relation to nature, man, and social life, traditions, customs, and various human states like joy, longing and others.